2017
DOI: 10.1111/glob.12182
|View full text |Cite
|
Sign up to set email alerts
|

How did the financial crisis affect the transnationality of the global financial elite? One step forward and one step back

Abstract: Over the last few decades, transnational elite formation progressed hand in hand with a deterioration in national business elites. Most studies regard this process as progressive and linear. However, we argue that transnational elite formation is subject to a variety of opposing forces, and the assumed progression is not a given fact. As an intriguing case, we analyse the financial business elite with a focus on the financial crisis of 2008. This international event had substantial ramifications, including a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, some studies have shown how these transnational business elites use transnational networks to control markets (Buch‐Hansen & Henriksen, 2019). In recent years, these transnational networks appear to have expanded to China (De Graaff, 2020), and this has not been slowed down by recent financial crises (Heemskerk et al., 2016; Van Veen, 2018). By using the nationality variable, the main contribution of these studies is to have identified directors who cross national borders and create transnational networks by sitting on multiple boards of large companies.…”
Section: Globalization and Transnational Business Elitesmentioning
confidence: 99%
“…Additionally, some studies have shown how these transnational business elites use transnational networks to control markets (Buch‐Hansen & Henriksen, 2019). In recent years, these transnational networks appear to have expanded to China (De Graaff, 2020), and this has not been slowed down by recent financial crises (Heemskerk et al., 2016; Van Veen, 2018). By using the nationality variable, the main contribution of these studies is to have identified directors who cross national borders and create transnational networks by sitting on multiple boards of large companies.…”
Section: Globalization and Transnational Business Elitesmentioning
confidence: 99%
“…Battiston & Catanzaro, 2004a). Studies of international board networks have over the years gave insights into the networks in business societies and the global economy (Fennema & Heemskerk, 2018), and how these have developed (Heemskerk et al., 2016a; Van Veen, 2018). However, such studies have been strongly biased towards the ‘corporate elites’ (Cárdenas, 2015; Heemskerk et al., 2016b), i.e.…”
Section: Network Of Board Interlocksmentioning
confidence: 99%
“…Today, the study of financial elites is a vibrant though developing area of study within the renewed field of elite studies, also attracting attention within the literature on financialisation (Beaverstock et al, 2013; Bellamy Foster and Holleman, 2010; Elliott and Atkinson, 2009; Van Veen, 2018). However, as we explore in this article, the study of financial elites is not straightforward.…”
Section: Introductionmentioning
confidence: 99%